Composting Rate of Household Organic Waste at Various Concentrations of Rice Water MOL - Bayu, Kadek Agus Krisna; Madrini, Ida Ayu Gede Bintang; Wijaya, I Made Anom Sutrisna (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Composting is one of solutions in household organic waste processing. The purpose of the research was to determine the rate of household organic waste composting at different concentrations of rice water MOL and to obtain the concentration of rice water MOL that produce the best household organic waste compost that accordance with minimum technical requirements of solid compost based on Decree of the Minister of Agriculture of Republic Indonesia No.261/KPTS/SR.310/M/4/2019. The treatment used 30 kg of household organic waste for one treatment and each concentrations of rice water MOL was 0 ml (control), 30 ml, 60 ml, 90 ml, 120 ml, 150 ml. The six treatments were repeated 2 times so that obtain 12 experimental units. Observation parameters include initial material content, Total Plate Count (TPC), temperature, pH, water content, electrical conductivity, carbon, nitrogen, C/N ratio, organic matter (OM). The data obtained were analyzed using Descriptive Statistical Analysis Method. Result of the composting study for 1 month showed that all the treatments had different rates of composting. The result of compost has pH value 6,8 7,2, water content 25,97%-33,42%, C-organik 30,13%-34,14%, N-total 1,26%-2,21%, C/N ratio 13,63% 26,37%, and OM 51,95%-58,86%. The treatment of adding 120 ml rice water MOL to 30 kg of household organic waste is the best treatment because it can reached ambient temperature on the 25th day and reached neutral pH on the 21st day and has met requirements of solid compost based on the Decree of the Minister of Agriculture of the Republic Indonesia No.261/KPTS/SR.310/M/4/2019.